1996
DOI: 10.1007/bf01540916
|View full text |Cite
|
Sign up to set email alerts
|

The effects of retinoic acid on immunoglobulin synthesis: Role of interleukin 6

Abstract: Retinoic acid (RA) and its parent compound, retinol (ROH, vitamin A), have been recognized as important immunopotentiating agents. Previous studies from our laboratory have demonstrated that RA can augment formalin-treated Staphylococcus aureus (SAC)-stimulated immunoglobulin (Ig) synthesis of cord blood mononuclear cells (CBMC). To determine the mechanism(s) by which RA modulates Ig synthesis, we studied the effects of RA on B cells and cytokine production. The addition of RA (10(-5) to 10(-10) M) to Epstein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
1
20
0
2
Order By: Relevance
“…Purified Tcells (>95% ) were obtained from adenoidal tissues from young children (ages 2-5) as previously described [5,8], RA at optimal concentrations (10 7M) was added to T cells (1x10'' cclls/ml) in culture plates. Controls included cultures to which the DMSO solvent/media was added at the same concentration as used to dissolve the RA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified Tcells (>95% ) were obtained from adenoidal tissues from young children (ages 2-5) as previously described [5,8], RA at optimal concentrations (10 7M) was added to T cells (1x10'' cclls/ml) in culture plates. Controls included cultures to which the DMSO solvent/media was added at the same concentration as used to dissolve the RA.…”
Section: Methodsmentioning
confidence: 99%
“…These properties range from the pro motion ofT lymphocyte proliferation to augmenting immu noglobulin (Ig) synthesis [1][2][3][4]. Our laboratory has been in terested in the effects of all-/ra«.v-retinoic acid (RA) in aug menting formalin-treated staphylococcus-stimulated B cell Ig production, and the mechanism by which this augmenta tion in Ig synthesis occurs [1,5,6], Both IL-2 and IL-6 are important cytokines for B cell differentiation and Ig secre tion [7], Recent studies in our laboratory suggest that the Ig-augmenting effects of RA is mediated, at least in part, by IL-6 through autocrine or paracrine pathways [8] This article is also accessible online at: http://www.karger.ch http://BioMedNct.com/karger direct effect of RA on T cells [1], We propose that RA can modulate other cytokines, c.g. IL-2, and that this effect may be mediated through specific RA nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, vitamin A deficient children were found to have lower naive and higher memory T cell percentages in blood, and these numbers were reversed by treatment with vitamin A [35] . In other human studies, vitamin A deficiency resulted in decreased cellmediated immune function [36,37] and antibody responses [36] and in lower numbers of CD4+ lymphocytes, all which also normalized following vitamin A administration [30,35,38].…”
Section: Immunological Effects Of Retinoidsmentioning
confidence: 76%
“…In animals, retinoids have been generally shown to suppress proinflammatory responses in activated immune cells [24,25,26,27,28,29,30] . In contrast, vitamin A deficiency in experimental animals is characteristically associated with enhanced proinflammatory immune responses, effects that can be reversed by vitamin A supplementation [31,32,33,29,34] .…”
Section: Immunological Effects Of Retinoidsmentioning
confidence: 99%
“…Retinoic acid-dependent gene expression of cytokines has been described. For instance, RA induces the transcription of inflammatory cytokines including IL-6 in HL-60 granulocytes and B-cells (Grande et al 1995;Ballow et al 1996). In contrast, IL-6 production in medulloblastoma cells (Liu et al 2000) and LIF expression in human osteoblasts have been reported to be suppressed by RA (Ahmed et al 2000).…”
Section: Introductionmentioning
confidence: 95%